The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/molecules23071563
|View full text |Cite
|
Sign up to set email alerts
|

Interference of Quercetin on Astragalus Polysaccharide-Induced Macrophage Activation

Abstract: Polysaccharides, which exert immunoregulatory effects, are becoming more and more popular as food supplements; however, certain components of ordinary foods could be reducing the polysaccharides beneficial effects. Quercetin, a flavonoid found in common fruits and vegetables, is one such component. This study investigated the effects of quercetin on Astragalus polysaccharide RAP induced-macrophage activation. The results show quercetin decreases the NO production and iNOS gene expression in RAW264.7 cells, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Macrophagelike cells usually exhibited three major morphologies, such as rounded, elongated, and significantly branched extensions . The RAW264.7 cells’ morphologies in the control group were round or oval as normal morphology, while the cells’ morphology changed after being treated with PSPP-1 and LPS, which could be obviously seen with a larger volume and some antennas around the cells (Figure ).…”
Section: Results and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Macrophagelike cells usually exhibited three major morphologies, such as rounded, elongated, and significantly branched extensions . The RAW264.7 cells’ morphologies in the control group were round or oval as normal morphology, while the cells’ morphology changed after being treated with PSPP-1 and LPS, which could be obviously seen with a larger volume and some antennas around the cells (Figure ).…”
Section: Results and Discussionmentioning
confidence: 94%
“…Macrophagelike cells usually exhibited three major morphologies, such as rounded, elongated, and significantly branched extensions. 21 The RAW264.7 cells' morphologies in the control group were round or oval as normal morphology, while the cells' morphology changed after being treated with PSPP-1 and LPS, which could be obviously seen with a larger volume and some antennas around the cells (Figure 2). At the concentration of 160 μg/mL, RAW264.7 exhibited hypertrophic cell bodies with ramified antennas, and the number of antennas increased markedly; such a morphology could increase the area of contact with outer substances and was helpful to the phagocytic uptake.…”
Section: ■ Results and Discussionmentioning
confidence: 94%
“…In RAW264.7 cells, an Astragalus polysaccharide-rich fraction mixed with plant flavonoid quercetin (19) decreased NO production and iNOS gene expression, although quercetin alone had no effect. The combination of the polysaccharide fraction and quercetin inhibited cytokine production, cellular phosphorylation, and ultimately macrophage activation in the RAW264.7 cells,[59] and the polysaccharide fraction alone upregulated the production of NO, TNF-α, IL-6, and iNOS genes. More importantly, these findings indicated that the immunomodulatory effect of the polysaccharide fraction was mediated via the activation of the NF-κB p65/mitogen-activated protein kinase (MAPK) signaling pathway.…”
Section: Actions Of the Nuclear Factor-kappa B Pathway In Immune Regu...mentioning
confidence: 99%
“…Radix Astragali (Astragalus membranaceus or "Huang Qi") is one of the most important "Qi" tonic herbs in traditional Chinese medicine (TCM) and is commonly used for enhancing the immune system and strengthening the physique (Auyeung et al, 2016;Li et al, 2018). A water soluble polysaccharide with an average molecular weight of 1334 kDa was named RAP, which was composed of Rha, Ara, Glc, Gal, and GalA in a molar ratio of 0.03:1.00:0.27:0.36:0.30, has been shown to have various biological effects, such as immunomodulation and antitumor, anti-inflammatory, and antioxidant activities (Song et al, 2008;Yin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%